Something About h - Measures of Sets in Plane - Bărbulescu Alina (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2014)
In this article we estimate the Hausdorff h-measures of the graphs of some functions, for different measure functions.